2020
DOI: 10.1186/s12906-020-2867-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allodynic effect induced by curcumin in neuropathic rat is mediated through the NO-cyclic-GMP-ATP sensitive K+ channels pathway

Abstract: Background: Recent studies pointed up that curcumin produces an anti-nociceptive effect in inflammatory and neuropathic pain. However, the possible mechanisms of action that underline the anti-allodynic effect induced by curcumin are not yet established. The purpose of this study was to determine the possible anti-allodynic effect of curcumin in rats with L5-L6 spinal nerve ligation (SNL). Furthermore, we study the possible participation of the NOcyclic GMP-ATP-sensitive K + channels pathway in the anti-allody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Lee et al [ 161 ] reported that intrathecal administration of curcumin alleviated SNL-induced allodynia, but they did not explore the underlying mechanisms of action. On the other hand, Pastrana-Quintos et al [ 160 ] reported that both oral and intrathecal curcumin induced anti-allodynic activity in an SNL model of neuropathic pain and that the anti-allodynic effect was mediated via the nitric oxide-cyclic guanosine monophosphate-adenosine triphosphate-sensitive potassium + channels pathway. Furthermore, the highest dose of oral (310 mg/kg) and intrathecal (0.3 mg) curcumin exerted maximal anti-allodynic effects, and intrathecal curcumin even produced significantly higher anti-allodynic activity compared to gabapentin [ 160 ].…”
Section: Curcumin and Neuropathic Pain—preclinical Studiesmentioning
confidence: 99%
“…Lee et al [ 161 ] reported that intrathecal administration of curcumin alleviated SNL-induced allodynia, but they did not explore the underlying mechanisms of action. On the other hand, Pastrana-Quintos et al [ 160 ] reported that both oral and intrathecal curcumin induced anti-allodynic activity in an SNL model of neuropathic pain and that the anti-allodynic effect was mediated via the nitric oxide-cyclic guanosine monophosphate-adenosine triphosphate-sensitive potassium + channels pathway. Furthermore, the highest dose of oral (310 mg/kg) and intrathecal (0.3 mg) curcumin exerted maximal anti-allodynic effects, and intrathecal curcumin even produced significantly higher anti-allodynic activity compared to gabapentin [ 160 ].…”
Section: Curcumin and Neuropathic Pain—preclinical Studiesmentioning
confidence: 99%
“…In these models, animals develop chronic inflammatory pain. Thus, in particular by its anti-inflammatory action, curcumin reduced mechanical and thermal hypersensitivity in the CCI model in SD rats [ 53 , 54 , 55 ], in Wistar rats [ 56 ], in male C57BL/6J mice [ 57 ], and in nerve ligature model in female Wistar rats [ 58 ] and in BALB/c mice [ 59 ]. Finally, curcumin also showed antinociceptive properties in SD rats in models of brachial plexus avulsion [ 60 ], alcohol-induced neuropathy in male and female Wistar rats [ 61 , 62 ], opioid-induced hyperalgesia in C57-BL/6J mice [ 63 ], HIV-gp120-induced neuropathic pain in male SD rats [ 64 ], and complete Freund’s adjuvant-induced inflammatory pain in Charles-Foster strain rats [ 65 ].…”
Section: Curcumin Studies In Animal Models Of Pnmentioning
confidence: 99%
“…Several studies have evaluated the potential analgesic effects of glibenclamide and other SUR agonists/antagonists in conjunction with other analgesics vis-à-vis K ATP channels in neuropathic pain [ 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 ]. In these studies, single doses of glibenclamide did not influence pain thresholds but they did blunt the anesthetic effects of the analgesic being tested.…”
Section: Sur1-trpm4 Expression and Inhibition In Other Neurological Conditionsmentioning
confidence: 99%